Effects of a 4-week youth baseball conditioning program on throwing velocity - Escamilla, R. F.; Fleisig, G. S.; Yamashiro, K.; Mikla, T.; Dunning, R.; Paulos, L.; Andrew, J. R. (The Journal of Strength and Conditioning Research, 2010)
This study examined the effects of a 4-week youth baseball conditioning program on maximum throwing velocity. Thirty-four youth baseball players (11-15 years of age) were randomly and equally divided into control and training groups. The training group performed 3 sessions (each 75 minutes) weekly for 4 weeks, which comprised a sport specific warm-up, resistance training with elastic tubing, a throwing program, and stretching. Throwing velocity was assessed initially and at the end of the 4-week conditioning program for both control and training groups. The level of significance used was p < 0.05. After the 4-week conditioning program, throwing velocity increased significantly (from 25.1 ± 2.8 to 26.1 ± 2.8 m/s) in the training group but did not significantly increase in the control group (from 24.2 ± 3.6 to 24.0 ± 3.9 m/s). These results demonstrate that the short-term 4-week baseball conditioning program was effective in increasing throwing velocity in youth baseball players. Increased throwing velocity may be helpful for pitchers (less time for hitters to swing) and position players (decreased time for a runner to advance to the next base).